1983
DOI: 10.1161/01.hyp.5.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic neurotransmission in tail arteries from two-kidney, one clip, renal hypertensive rats.

Abstract: SUMMARY The goal of this study was to determine if increased vascular smooth muscle sensitivity to norepinephrine in two-kidney, one clip (2K1C) hypertensive rats is the result of a decrease in adrenergic nerve function. Vascular sensitivity to norepinephrine was measured in isolated tail artery strips from 2K1C hypertensive and normotensive rats and in various arterial strip preparations from normotensive rats that exhibit varying degrees of adrenergic innervation. In each case, the characteristic of the vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…norepinephrine was also increased in these vessels [32], Increased vascular sensitivity in hypertensive rats to exogenous catechol amines has been reported previously. For example, Lais and Brody [33] found that the threshold constrictor response to norepi nephrine in the denervated hindquarters of spontaneously hypertensive rats is only one third that of NT rats.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…norepinephrine was also increased in these vessels [32], Increased vascular sensitivity in hypertensive rats to exogenous catechol amines has been reported previously. For example, Lais and Brody [33] found that the threshold constrictor response to norepi nephrine in the denervated hindquarters of spontaneously hypertensive rats is only one third that of NT rats.…”
Section: Discussionsupporting
confidence: 80%
“…An alternative explanation is the conversion of spare ct]-adrenoceptors, which Ruffolo and Yaden [35] have shown to be present in rat vasculature, to functional a r adrenoceptors. Such comparable increases in sensitivity may also suggest that: (i) in the tail artery, both extrajunctional ap and 012-adrenoceptors are stimulated by the same store of presynaptic norepinephrine, which is depleted in the RHT rat [32], or (ii) that sympathetic innervation to the tail arteries is decreased in the RHT rat, and that such a decrease has a comparable effect on neurons which stimulate extrajunctional Cb-adrenoceptors as well as neurons which stimulate extrajunctional ct|-adrenoceptors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The case for potassium is more com plicated. Potassium-induced contractions of poorly innervated vascular smooth muscles, such as aorta, are independent of noradrena line release [Shibata and Carrier, 1967], Such contractions are not inhibited by aadrenoreceptor blocking agents such as phentolamine (10~4 A/) or by reserpine [Garret and Carrier, 1971], In the densely innervated rat tail artery, phentolamine (1 O'6 or 10-5 M) inhibits 35-50% of the vasocon striction induced by potassium [Webb et al, 1978[Webb et al, , 1983. We found that phentol amine (4 X 10~b M ) blocks potassium-in duced vasoconstriction (40 mM) by 95% [unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a general increase in the reactivity to a wide variety of vasoconstrictor agents. Others have reported, however, that whilst responses to exogenous noradrenaline are increased, vasoconstrictor responses to stimuli that release endogenous noradrena line are not modified [Lais et al, 1974;Collis and Vanhoutte, 1977], Likewise, it has been reported that renovascular hyper tension in the rat is accompanied by struc tural adaptation of the vessel wall similar to that occurring in the SHR [Lundgren et al, 1974] and that responses to endogenous and exogenous noradrenaline are different: there is a decrease in the response to en dogenous noradrenaline and an increase in the response to exogenous noradrenaline [Webb et al, 1983].…”
Section: Introductionmentioning
confidence: 98%